Upper motor neurone syndrome and spasticity : clinical management and neurophysiology - Barnes, Michael P., 1952-; Johnson, Garth R., 1945- (Cambridge : Cambridge University Press, 2008)
Spasticity is a disabling problem for many adults and children with a variety of neurological disorders such as multiple sclerosis, stroke, cerebral palsy and traumatic brain injury. A practical guide for clinicians involved in the management of spasticity, this book covers all aspects of upper motor neurone syndrome from basic neurophysiology and measurement techniques to practical therapy and the use of orthoses. Surgical techniques are also covered, as well as the particular problems of management of spasticity in childhood. In the second edition of this key text, all chapters have been thoroughly updated, with additional coverage of new techniques and new drugs and therapies, whilst continuing the format that has made the first edition the core text in its field. This guide will be invaluable to physicians, physiotherapists, surgeons, orthotists, clinical engineers and health professionals.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Spasticity; Motor neurons -- Diseases